Мораль: духовна культура чи ідеологія? - Іваї Хатіро (Народна творчість та етнографія, 2009)
The prospects of returning of the Japanese society to the system of its traditional moral values and methods of warning of this process politization are examined in the article. The peculiarities of the Japanese behavior model are covered in the context of the European system of values. Considerable attention is given to the description of the changes of moral norms and stereotypes which got distribution in Japan at the end of the 20th century.